(untitled) (Research, Society and Development, 2022)
This study, through a descriptive and exploratory methodology, aims to carry out a diagnosis in companies that provide services of air conditioning systems, agreeing on the application of Law No. 13,589 of 2018 and of Ordinance No. 3,523 of August 28th, 1998, Brazilian legislation that is in force and deals mainly with the obligation to have a Maintenance, Operation and Control Plan (MOCP) in public and collective buildings, which have artificially air-conditioned environments, the aim is also to proffer the importance of MOCP as a way of controlling contaminants to achieve good indoor air quality (IAQ), which has become a topic of global importance, mainly due to its ability to provide users with physical and mental damage, this is also superimposed on Resolution No. 9/2003, a rule created by the National Health Surveillance Agency, (ANVISA), which promotes control parameters that configures as acceptable requirements for the concentration of harmful substances exposed in the air of indoor environments. For the diagnosis, the Survey technique was adopted, and, in the data collection stage, a questionnaire was used based on consultations with legislation and bibliographic references. As a result, it was possible to measure that there are organizations, the contractors, that do not comply with the MOCP and that some doubts still arise from applying the legislation. Thus, these nonconformities lack the possibility of creating action plans to raise awareness, clarify and help providers and organizations to adapt to legal parameters.